39 Reproductive challenges of cattle adapted to tropical and subtropical environments. (5th December 2019) - Pohler, Ky; Reese, Sydney T; Franco, Gessica Aruajo; Filho, Ramiro Oliveira; Montero, Lohana Fernandez; Melo, Gabriela Dalmaso de; Moraes, Ana
Abstract: In the coming decades, tropical and subtropical regions of the world, including southern United States, southeast Asia, India, parts of Africa and Central and South America, will experience both the greatest increases in population and demands for beef. Potential for expansion of beef production in these areas is considerable due to abundance and low cost of forages that are a non-competitive food source for humans; however, research efforts must emphasize cattle efficiency to maximize sustainability of the cattle industry. Raising tropically adapted cattle in these regions present unique opportunities and challenges that differ from strategies used in production of the predominant B. taurus cattle common in temperate regions of the globe. Despite the physiological differences between B. taurus and B. indicus cattle including reproductive physiology, nutritional requirements, social behavior, digestive system, and body composition, strategies developed in B. taurus cattle are commonly used for B. indicus production. Hence, a fundamental step to meet the increasing global demand for protein while addressing environmental stewardship is to identify these physiological, social and nutrient requirement differences to develop, and disseminate management practices tailored to optimizing production efficiency of B. indicus-influenced cattle reared in subtropical/tropical regions of the planet. From a reproductive management perspective, tropically adapted cattle present several challenges including increased age at puberty, increased postpartum anestrous period and managed in an extensive system. Additionally, reproductive failures post pregnancy establishment are known to be greater in B. indicus cattle in tropical/subtropical regions, although the exact reasons for this outcome have not been identified and addressed. This talk will focus on recent research and strategies aimed at mitigating the impacts of reproductive inefficiency in tropically adapted cattle.